Love as morality - Matei, Alexandru (Primerjalna književnost, 2016)
A Lover's Discourse. Fragments is one of the most read text on love by the end of the twentieth century. Considered within the larger span of Roland Barthes's works, his Fragments are a sort of preview for the main affective utopia Barthes ever dreamt of: the Neutral, as closeness and distance at the same time. The main trigger of Barthes febrile research of the Neutral is his conception of an affect apt to be separated from power. Love without exerting any pressure on the other. One of its origins may be considered his own difference: being homosexual in a society deprived of institutions meant to shelter homosexual affection.
Keywords: Barthes, Roland: A lover's discourse; ljubezen; love; teorija čustev; jezik in moč